Injury patterns among elite football players: A media-based analysis over 6 seasons with emphasis on playing position - Leventer, L.; Eek, F.; Hofstetter, S.; Lames, M. (International Journal of Sports Medicine, 2016)
The study objective was to describe the types, localizations and severity of injuries among first division Bundesliga football players, and to study the effect of playing position on match and training injury incidence and severity, based on information from the public media. Exposure and injuries data from 1448 players over 6 consecutive seasons were collected from a media-based register. In total, 3358 injuries were documented. The incidence rate for match and training injuries was 11.5 per 1000 match-hours (95% confidence interval [CI]: 10.9-12.2), and 61.4 per 100 player-seasons (95% CI: 58.8-64.1), respectively. Strains (30.3%) and sprains (16.7%) were the major injury types, with the latter causing significantly longer lay-off times than the former. Significant differences between the playing positions were found regarding injury incidence and injury burden (lay-off time per incidence-rate), with wing-defenders sustaining significantly lower incidence-rates of groin injuries compared to forwards (rate ratio: 0.43, 95% CI: 0.17-0.96). Wing-midfielders had the highest incidence-rate and injury burden from match injuries, whereas central-defenders sustained the highest incidence-rate and injury burden from training injuries. There were also significant differences in match availability due to an injury across the playing positions, with midfielders sustaining the highest unavailability rates from a match and training injury. Injury-risk and patterns seem to vary substantially between different playing positions. Identifying positional differences in injury-risk may be of major importance to medical practitioners when considering preventive measures.